2019
DOI: 10.1029/2019gl082034
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Acetaldehyde: Importance of Air‐Sea Exchange and a Missing Source in the Remote Troposphere

Abstract: We report airborne measurements of acetaldehyde (CH3CHO) during the first and second deployments of the National Aeronautics and Space Administration Atmospheric Tomography Mission (ATom). The budget of CH3CHO is examined using the Community Atmospheric Model with chemistry (CAM‐chem), with a newly developed online air‐sea exchange module. The upper limit of the global ocean net emission of CH3CHO is estimated to be 34 Tg/a (42 Tg/a if considering bubble‐mediated transfer), and the ocean impacts on tropospheri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
75
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(82 citation statements)
references
References 99 publications
7
75
0
Order By: Relevance
“…It is proposed that the oceans serve as a net source for atmospheric acetaldehyde through air‐sea exchange; however, fluxes vary widely (Beale et al, 2013; Millet et al, 2010; Singh et al, 2004; Zhu & Kieber, 2019). An annual global sea to air flux of 34–57 Tg year −1 was calculated using an oceanic mixed‐layer photochemical flux model, with remotely sensed chromophoric dissolved organic matter (CDOM) absorption used as model input as a proxy to extrapolate rate data to the oligotrophic ocean (Millet et al, 2010; Wang et al, 2019). This modeled flux is substantially greater than the global sea‐to‐air acetaldehyde flux of ~3–17 Tg year −1 calculated based on in situ observations across the Atlantic Ocean (Beale et al, 2013; Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…It is proposed that the oceans serve as a net source for atmospheric acetaldehyde through air‐sea exchange; however, fluxes vary widely (Beale et al, 2013; Millet et al, 2010; Singh et al, 2004; Zhu & Kieber, 2019). An annual global sea to air flux of 34–57 Tg year −1 was calculated using an oceanic mixed‐layer photochemical flux model, with remotely sensed chromophoric dissolved organic matter (CDOM) absorption used as model input as a proxy to extrapolate rate data to the oligotrophic ocean (Millet et al, 2010; Wang et al, 2019). This modeled flux is substantially greater than the global sea‐to‐air acetaldehyde flux of ~3–17 Tg year −1 calculated based on in situ observations across the Atlantic Ocean (Beale et al, 2013; Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 64%
“…Earlier versions of TOGA had difficulty measuring some carbonyls in clean-air conditions (including acetone and acetaldehyde; Apel, 2003); however, neither the original studies nor more recent updates have suggested that there are any issues in measuring MEK. Changes to TOGA have lowered detection limits and increased the capability of the instrument in measuring carbonyl mixing ratios in clean conditions (Apel et al, 2015;Wang et al, 2019). Further discussion of the tests performed regarding these measurement artifacts in preparation for the ATom campaigns can be found in the supplementary material to this work (for MEK and acetone) and in the supplement to Wang et al (2019).…”
Section: Observations Of Mekmentioning
confidence: 99%
“…Changes to TOGA have lowered detection limits and increased the capability of the instrument in measuring carbonyl mixing ratios in clean conditions (Apel et al, 2015;Wang et al, 2019). Further discussion of the tests performed regarding these measurement artifacts in preparation for the ATom campaigns can be found in the supplementary material to this work (for MEK and acetone) and in the supplement to Wang et al (2019). Data from both WAS and TOGA registering below the lower limit of detection (LLOD) were dynamically assigned a value between 0 and the LLOD as a linear function of how many LLOD-flagged values were recorded on a given flight: the more LLOD-flagged non-NA observations, the closer the assigned value was to 0.…”
Section: Observations Of Mekmentioning
confidence: 99%
See 2 more Smart Citations